The January 1, 2024, Noto Peninsula, Japan, MW7.5 earthquake as a plausible 'Dragon King' event - Yue Liu; Zhongliang Wu; Yongxian Zhang (地球与行星物理论评, 2024)
We discussed the relation among 'black swan', 'gray rhino' and 'dragon king', three important concepts in the study for the reduction of natural disaster risks, in which a 'black swan' refers to 'an event that, seems to us, on the basis of our limited experience, to be impossible' (Taleb, 2007), a 'gray rhino' refers to 'an event that is dangerous, obvious, and highly probable' (Wucker, 2016), and a 'dragon king' is defined as 'an event so extreme that it lies outside a power-law distribution' (Sornette and Ouillon, 2012), all of which have some misinterpretations. We investigated whether the January 1, 2024, Noto Peninsula, Japan, MW7.5 earthquake, which punctuated the intense and long-lasting swarm since recent years, can be regarded as a 'black swan' or a 'dragon king', which seems an interesting question in the study of earthquake forecast and prediction. The answer to the question whether or not this MW7.5 earthquake is a 'black swan' depends on the observer, by the definition of 'black swan': in the sense that this earthquake unexpectedly punctuated the intense and long-lasting swarm, it is; while in the sense that there have been historical earthquakes with comparable magnitudes in the same region, it is not. Whether or not this earthquake is a 'dragon king' event is the main topic of this paper, which depends on the analysis of earthquake data. We analyzed the seismic moment tensor catalogue of the Japan Meteorological Agency (JMA) which has started since 2004. We inspected the rank-ordering plot or Zipf distribution to inspect whether the MW7.5 event behaves as an outlier which significantly deviates from the Gutenberg-Richter power law scaling. We obtained that for the period 2006 to 2024, the MW7.5 earthquake cannot be regarded as a significant 'dragon king' event, while for the period 2021 to 2024 the earthquake can be regarded as a 'dragon king' event significantly, which seems consistent with the report that complex precursory behavior has occurred since December 2020, implying the predictability of this 'dragon king' event. We suggest that detailed study of this earthquake as well as its aftershock sequence, based on the previous results of investigation which provided with good pictures of fluid migration, silent earthquakes, deformation, and earthquakes with different magnitudes, plus retrospective case study of the precursor-like anomalies in this relatively isolated system of seismicity, may contribute to the theory of the mechanism and prediction of a 'seismic dragon king'.